2010
DOI: 10.1111/j.1744-7917.2010.01333.x
|View full text |Cite
|
Sign up to set email alerts
|

Gene cloning and expression of aminopeptidase N and cadherin from midgut of the rice stem borer, Chilo suppressalis

Abstract: The rice stem borer, Chilo suppressalis Walker is one of the most important insect pests on rice in Asia, north Africa and southern Europe. Transgenic Bt rice has been developed in the laboratory with good resistance to this pest and other Lepidopteran insects, which will provide a possible alternative tool for this pest control. The full-length cDNAs encoding an aminopeptidase N (CsAPN) and a cadherin (CsCad) were cloned from C. suppressalis. CsAPN showed common features of, and high identities to, other inse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 27 publications
2
14
0
Order By: Relevance
“…Spot 74 was identified as EH domain-containing protein 1, but spot 73 had no significant match (Table S3). These results confirmed that APN binds with the Cry1Ac toxin [39]. To the best of our knowledge, this is the first report that EH domain-containing protein 1 interacts with Bt toxins, and this result should be confirmed by further study.…”
Section: Resultssupporting
confidence: 79%
“…Spot 74 was identified as EH domain-containing protein 1, but spot 73 had no significant match (Table S3). These results confirmed that APN binds with the Cry1Ac toxin [39]. To the best of our knowledge, this is the first report that EH domain-containing protein 1 interacts with Bt toxins, and this result should be confirmed by further study.…”
Section: Resultssupporting
confidence: 79%
“…suppressalis APN and CAD‐like proteins are involved in Cry toxicity in C . suppressalis (Yu et al ., ; Ma et al ., ; Qiu et al ., ; Wang et al ., ). The goal of this study was to determine if ALPs might also act as potential Cry1A, Cry2A and Cry1C receptors in the midgut of C .…”
Section: Discussionmentioning
confidence: 97%
“…suppressalis than nontransgenic rice (Tu et al ., ; Chen et al ., ; Tang et al ., ; Zhao et al ., ). Previous studies have suggested that APN and cadherin‐like (CAD‐like) proteins act as Cry toxin binding proteins (Yu et al ., ; Ma et al ., ; Wang et al ., ). We have previously found evidence to suggest that APN1 and APN2 are involved in the toxicity of Bt transgenic rice to C .…”
Section: Introductionmentioning
confidence: 97%
“…Proteomic studies identified APN isoforms (approximately 130 and 150 kDa) and an EH domain-containing protein 1 (approximately 80 kDa) as Cry1Ac binding proteins in C. suppressalis BBMV (21). In comparison, a 119-kDa APN and a 197-kDa cadherin were reported to bind Cry1Ab on ligand blots of C. suppressalis BBMV (20). Considering that Cry1Ab and Cry1Ac toxins share all binding sites in BBMV of C. suppressalis (19), we speculate that the 115-and 200-kDa proteins detected in our Cry1Ac ligand blots may represent the 119-kDa APN and 197-kDa cadherin, respectively, reported to bind Cry1Ab.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of C. suppressalis, binding competition studies in larval brush border membrane vesicles (BBMV) revealed that Cry1A toxins share binding sites with Cry1Ba toxin (17) but they are not recognized by Cry2A, Cry9C, or Cry1C toxins (18,19). Diverse studies have suggested aminopeptidase-N and cadherin-like proteins as Cry1A binding sites in C. suppressalis BBMV (20,21). In contrast, no Cry toxin binding data are available for S. inferens.…”
mentioning
confidence: 99%